2000
DOI: 10.1046/j.1471-4159.2000.0742067.x
|View full text |Cite
|
Sign up to set email alerts
|

p‐Ethynylphenylalanine

Abstract: Tryptophan hydroxylase (TPH) is the initial and rate-limiting enzyme in serotonin biosynthesis. The enzyme activity is dependent on molecular oxygen, a tetrahydropterin cosubstrate, and ferrous iron. The present study demonstrates that TPH is inhibited by a novel compound, p-ethynylphenylalanine (pEPA), produced by the Heck reaction of trimethylsilylacetylene with N-tertbutyloxycarbonyl-4-iodo-L-phenylalanine methyl ester. pEPA is a more potent and specific inhibitor of TPH than p-chlorophenylalanine (pCPA). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The present in vitro assays suggested that QN competes directly with tryptophan for binding to the active site of TPH2, similar to the known competitive TPH2 inhibitor, pCPA31. pCPA potently decreases serotonin production in the brain31.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The present in vitro assays suggested that QN competes directly with tryptophan for binding to the active site of TPH2, similar to the known competitive TPH2 inhibitor, pCPA31. pCPA potently decreases serotonin production in the brain31.…”
Section: Discussionsupporting
confidence: 57%
“…The present in vitro assays suggested that QN competes directly with tryptophan for binding to the active site of TPH2, similar to the known competitive TPH2 inhibitor, pCPA31. pCPA potently decreases serotonin production in the brain31. The inference that QN, similarly, may have the potential to suppress serotonin production by cells was borne out by analysis of serotonin levels in RN46A cells and, in particular, yeast cells.…”
Section: Discussionmentioning
confidence: 54%
“…This drug has not been studied extensively in humans, but it was found to reduce urinary excretion of 5-HIAA and the emetic response in chemotherapy patients [19]. Other methods to decrease levels of 5-HT, like using 6-fluorotryptophan, 5,7-dihydroxytryptamine, or creating lesions in the raphe nucleus have had limited success in animal models [20]. P-ethynylpheny-lalanine is a newer irreversible inhibitor of tryptophan hydroxylase, which was found to be more potent and more specific to tryptophan hydroxylase than pCPA.…”
Section: Discussionmentioning
confidence: 99%
“…P-ethynylpheny-lalanine is a newer irreversible inhibitor of tryptophan hydroxylase, which was found to be more potent and more specific to tryptophan hydroxylase than pCPA. However, this drug has not been studied in humans [20,21]. …”
Section: Discussionmentioning
confidence: 99%